Analysis of the Implementation of the Teaching Factory Program in Vocational High School - Aulya Chasovy; Nizwardi Jalinus; Waskito; Rizky Ema Wulansari (Jurnal Penelitian Pendidikan IPA, 2024)
A production-based learning approach known as "Teaching Factory" is used in vocational schools. It is based on industry standards and processes conducted in an environment akin to that of the industry. However, based on previous research, there are several obstacles faced in implementing Teaching Factory in Vocational High Schools. This research aims to find out how the implementation of the Teaching Factory in Padang Vocational High School by conducting dissemination, planning, implementation, monitoring and evaluation. The samples in this research were SMK Negeri 1 West Sumatra, SMK Negeri 2 Padang, and SMK Negeri 9 Padang. Based on the results, it was found that first, there was no significant impact on the implementation of dissemination on the results of monitoring and evaluation of the Teaching Factory program at Padang Vocational High School, with percentage of 1.70%. Second, there is no significant change from planning on the results of monitoring and evaluation of the Teaching Factory program at Padang Vocational High School, with percentage of 11.90%. Third, there is a significant change from implementation on the results of monitoring and evaluation of the Teaching Factory program at Padang Vocational High School, with percentage of 27.10%. This shows that the success of a program can be achieved with good implementation